2008
DOI: 10.1021/ja802054k
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Contributions to Association in Polyelectrolyte Multilayers and Complexes: Visualizing Hydrophobicity

Abstract: Thin films of polyelectrolyte complex were assembled using the multilayering method with direct, in situ observation of all multilayer components using attenuated total internal reflectance FTIR (ATR-FTIR). Buildup and ion doping of two representative combinations of positive and negative polyelectrolytes are controlled by salt type. The internal hydration of multilayers, measured precisely by ATR-FTIR, depends on the chemical identities of the polymers and the salt ions. The efficiency of doping inversely tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
289
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(311 citation statements)
references
References 71 publications
21
289
1
Order By: Relevance
“…Data set H 2 O vac and D 2 O vac are the same. Error bars are set in accordance to a level of 10% increase in w 2 49 also reported hydration contributions to association in polyelectrolyte multilayers. Our analysis based on neutron reflectivity indicates no structural change in the dry polyelectrolyte multilayers, prepared from light water H 2 O, dried and subsequently exposed to heavy water D 2 O for 8 hours and then dried.…”
Section: Hydration Water In Polyelectrolyte Multilayersmentioning
confidence: 96%
“…Data set H 2 O vac and D 2 O vac are the same. Error bars are set in accordance to a level of 10% increase in w 2 49 also reported hydration contributions to association in polyelectrolyte multilayers. Our analysis based on neutron reflectivity indicates no structural change in the dry polyelectrolyte multilayers, prepared from light water H 2 O, dried and subsequently exposed to heavy water D 2 O for 8 hours and then dried.…”
Section: Hydration Water In Polyelectrolyte Multilayersmentioning
confidence: 96%
“…The solubility of anions increases with decreasing hydration entropy DH h according to the Hofmeister series (for ClO À 4 DH h ffi À57 J K À1 mol À1 and for SO 2À 4 DH h ffi À2000 J K À1 mol À1 ) [39]. The hydration number of anions follows the order ClO À 4 < NO À 3 % Cl À < SO 2À 4 [40,41]. Since the hydration number differs for every anion, small, hard ions form large water balls and transport large amounts of water with itself due to the high level of solvation [42].…”
Section: Bilayers In Fourmentioning
confidence: 99%
“…An important difference between chemically cross-linked hydrogels and PEMs is that the latter are ion-pair cross-linked films and therefore soluble salt plays an important role controlling the degree of crosslinking. [28][29][30] For instance, we have previously shown that the…”
Section: Introductionmentioning
confidence: 99%